PARP-1-modulated AIF translocation is involved in streptomycin-induced cochlear hair cell death - Song, Yongdong (Acta Otolaryngol, 2016)
CONCLUSION: SM-induced dose- and location-dependent cochlear hair cell death in vitro. AIF might be translocated from mitochondria to nucleus and cytoplasm within SM-treated hair cells. The translocation of AIF might be modulated by PARP-1. OBJECTIVE: Streptomycin (SM), one of the widely used aminoglycoside nowadays, is still causing significant permanent sensorineural hearing loss owing to sensory hair cell death. This study was designed to investigate the role of apoptosis-inducing factor (AIF), an important mitochondrial cell death regulator, in SM ototoxicity within neonatal rat cochleae and HEI-OC1 cells. METHODS: The viability of HEI-OC1 cells was quantified by MTT assay. AIF, PARP-1, and myosin VIIa distributions were achieved by immunofluorescence. mRNA and protein expression of AIF and PARP-1 were examined by q-PCR and Western-blot. RESULTS: The hair cell loss was concomitant with the SM concentration variation, and aggravated from apical to basal turn. AIF was detected in nuclear region and AIF mRNA was up-regulated after SM incubation. Besides, AIF protein expression in mitochondria was decreased, whereas in cytosol it was increased. PARP-1 mRNA and protein were also up-regulated. 3-AB could attenuate the cell death and reverse the changes of AIF distribution by blocking PARP-1.